Effects of child characteristics and dental history on dental fear: cross-sectional study - Mohammad A. Alshoraim; Azza A. El-Housseiny; Najat M. Farsi; Osama M. Felemban; Najlaa M. Alamoudi; Amani A. Alandejani (BMC, 2018)
Abstract Background Dental fear (DF) is a challenging problem in dentistry. It is multifactorial in origin and many contributing factors have been identified. The aim of the study was to assess dental fear among 12-15 years old Arabic speaking children in Jeddah, Saudi Arabia and its relation to demographic variables, previous dental experience, and child behaviour. Methods In this cross-sectional study, a total of 1522 boys and girls from middle schools in Jeddah, Saudi Arabia participated in this study during the period of 2014 to 2016. The Children's Fear Survey Schedule-Dental Subscale (CFSS-DS) was used to assess DF. A parental questionnaire was used to record the children's previous dental experience. Children were examined for caries and the children's behaviour was assessed during dental examination using Frankl Behaviour Rating Scale. The associations between different variables and the CFSS-DS scores were analysed using t-tests, ANOVA, and multiple linear regression analysis. Results The response rate of the questionnaires was 78.6%. The mean CFSS-DS score was 25.99 ± 9.3 out of a maximum of 75. Bivariate analysis showed that younger children, girls, and public-school students were significantly more fearful than older children, boys, and private school children, respectively (P < 0.001). Children who showed poor behaviour during dental examination were significantly more fearful than those with good behaviour (P < 0.001). Regression analysis showed that children who had significantly higher scores of dental fear were the children who did not visit the dentist in the past year due to dental fear; who never visited the dentist or those who only visited the dentist on pain; who were reported by parents as crying, screaming, or resistant during their previous dental visit; and those who were described to be in pain during previous dental treatment. Dental caries showed no significant association with DF. Conclusions This study confirms that DF is low among 12-15 years old Arabic speaking children in Jeddah, Saudi Arabia. DF is associated with age, gender, school type, irregular patterns of dental visits, painful experiences during previous dental visits and negative behaviours during dental examinations.